2008
DOI: 10.1007/s00384-008-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Positive impact of blocking tumor necrosis factor α on the nutritional status in pediatric Crohn’s disease patients

Abstract: In pediatric CD patients, infliximab seems to impact positively on the nutritional status as demonstrated by the improvement in weight and BMI, but not in linear growth; effects on nutritional status seem to be due to amelioration of disease activity, rather than to REE reduction or food intake increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
2
22
1
Order By: Relevance
“…The Z-scores for these patients significantly improved at both week 30 (mean improvement of 0.3) and week 54 (mean improvement of 0.5). In contrast to the study of Diamanti et al, 39 we found no significant impact of IFX treatment on the nutritional status. This difference may be due to a loss of power, since we showed a higher increase in the BMI Zscore in the ''IFX efficacy'' than in the ''IFX failure'' group, but this difference was not significant (P ¼ 0.24).…”
Section: Discussioncontrasting
confidence: 84%
“…The Z-scores for these patients significantly improved at both week 30 (mean improvement of 0.3) and week 54 (mean improvement of 0.5). In contrast to the study of Diamanti et al, 39 we found no significant impact of IFX treatment on the nutritional status. This difference may be due to a loss of power, since we showed a higher increase in the BMI Zscore in the ''IFX efficacy'' than in the ''IFX failure'' group, but this difference was not significant (P ¼ 0.24).…”
Section: Discussioncontrasting
confidence: 84%
“…TNFα is an inflammatory cytokine released by adipose tissue and is becoming recognised as an important component of normal energy homeostasis (Pamir et al, 2009; Endo et al, 2007). It has long been known that elevated TNFα might be an important component of the depressed appetite in disease and infection states (Langhans and Hrupka, 1999; Plata-Salaman et al, 1996; Sonti et al, 1996), such as cancer cachexia (Argiles et al, 2003; Argiles et al, 2005; Bernstein, 1996; Bernstein et al, 1991; Langstein et al, 1991; Smith and Kluger, 1993; Tisdale, 1999), Crohn’s disease (Diamanti et al, 2009), chronic obstructive pulmonary disease (Calikoglu et al, 2004) and infection (Truyens et al, 1995), as well as the anorexia induced by lipopolysaccharide injection (Arsenijevic et al, 2000; Kim et al, 2007; Porter et al, 1998; Tollner et al, 2000). Mice with the TNFα converting enzyme (TACE; also known as ADAM17) inactivated are hypermetabolic and lean (Gelling et al, 2008), whereas those with both TNF receptors knocked out are obese and insulin resistant (Pamir et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, its effect on growth is less obvious. The REACH study [86] showed an improvement of height z-score of 0.5 after 54 weeks of treatment in 112 children with moderate to severe CD, while Diamanti et al [90] reported no improvement of linear growth despite an increase in weight and BMI in a small sample of 14 subjects. Moreover, Pfefferkorn et al [5] found no significant improvement of height z-score in 176 children with a Tanner score between I and III but an increase in height velocity z-score after 2 years.…”
Section: Resultsmentioning
confidence: 99%